Acceptability of teleconsultation in a public service specialized in the prevention and care of HIV infection and other sexually transmitted infections. - Queiroz Rocha, Simone; Vono Tancredi, Mariza; Fonsi, Mylva; Lotufo Estevam, Denize; de Barros Tenore, Simone; Caricol Dell’Agnolo, Renata; Rodrigues, Rosangela; de Alencar Souza, Rosa (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: Telemedicine was leveraged for its contribution to mitigate the impact of COVID-19 in Brazil and worldwide. Objective: We aim to evaluate the acceptability of incorporating teleconsultation through synchronized videoconference by users and professionals in a service specialized in the prevention and treatment of the human immunodeficiency virus and other sexually transmitted infections, and to identify associated factors. Methods: This is a cross-sectional study with 410 users and 57 professionals who answered a category-standardized questionnaire. Predictors of acceptability were assessed using logistic regression model. Results: A total of 364 (88.8%) users said they would accept the modality. The factors positively associated with the odds of acceptance were the self-assessment of having favorable conditions to participate in a teleconsultation (aOR 54.8; 95%CI 12.4–242.1; p<0.001), the perception of saving money (aOR 5.2; 95%CI 1.9–14.0; p=0.001), and perceived convenience of the modality (aOR 6.7; 95%CI 2.9–15.9; p<0.001). Factors associated with reduced odds of acceptance were the fear of not being evaluated well (aOR 0.2; 95%CI 0.1–0.4; p<0.001), or remaining long without seeing the professional (aOR 0.2; 95%CI 0.1–0.5; p<0.001). The acceptance of the modality among professionals was 75.4% and the perception of its convenience (aOR 16.8; 95%CI 2.6–108.4; p=0.003) and that the institution has appropriated conditions (aOR 7.7; 95%CI 1.5–40.6; p=0.016) were associated with increased odds of accepting its incorporation in their routine. Conclusion: Governance should invest in infrastructure and support, secure protocols, digital literacy, and training of its users and employees for video teleconsultation.